Atributos de la artesanía como recurso turístico potencial, para la práctica del turismo cultural, en el distrito de catacaos, provincia de piura, departamento de piura - Yengle Villanueva, Yessenia Lissbeth (2016)
This research entitled Attributes of craftsmanship as a potential tourist resource for the practice of cultural tourism in the district of Catacaos, Piura province, Piura department, was oriented to identify, describe and analyze the attributes of crafts Catacaos ( the diversity of the craft, and the techniques used) as potential for the practice of cultural tourism tourist resource. The first thing to consider is the diversity of crafts district Catacaos guys posing as jewelry, pottery, straw and wood, the great diversity of the types of craftsmanship, materials are identified using a goldsmith's gold and silver, the use of clay pottery and clay, weavers use of straw shawl and used woodworking zapote tree. Secondly each artisan techniques used to prepare each of their various crafts, which are still passed down from generation to generation, goldsmiths used the technique of filigree gold and silver was considered, potters used the technique the paleteo, for making clay pottery and clay, for works in straw shawl using the technique of hand weaving and woodwork and carving technique is done. Stating that the craft is a potential to be practiced in cultural tourism tourist resource.